2017
DOI: 10.20886/ijfr.2017.4.2.85-94
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY AND GENETIC RELATIONSHIP OF SENGON (Falcataria moluccana) REVEALED USING SINGLE NUCLEOTIDE POLYMORPHISM (SNP) MARKERS

Abstract: GENETIC DIVERSITY OF SENGON (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) REVEALED USING SINGLE NUCLEOTIDE POLYMORPHISM (SNP) MARKERS. Knowledge on genetic diversity and relationship between population is important for genetic conservation and breeding program. This paper describes the use of Single Nucleotide Polymorphism (SNP) markers for genetic diversity and relationship of sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes). Twelve single nucleotide polymorphism (SNP) markers which were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Clarifying the genetic or phylogenetic relationships among organisms are greatly helpful for parent selection in breeding projects [56]. In the last three decades, the molecular markers such as RAPD, AFLP, SSR, SNP have played an important role to study the phylogenetic relationship of individuals among intra-and inter-species [57,58].…”
Section: Genetic Relationships Among Blueberry Cultivarsmentioning
confidence: 99%
“…Clarifying the genetic or phylogenetic relationships among organisms are greatly helpful for parent selection in breeding projects [56]. In the last three decades, the molecular markers such as RAPD, AFLP, SSR, SNP have played an important role to study the phylogenetic relationship of individuals among intra-and inter-species [57,58].…”
Section: Genetic Relationships Among Blueberry Cultivarsmentioning
confidence: 99%
“…Johnson and (2011) stated that plant growth is controlled by genetics, thus differences in genetic formation will affect the appearance of a particular character. Analysis of genetic diversity using RAPD, SSR, and SNP markers showed grouping between susceptible and resistant sengon plants (Shabrina 2020;Rahmawati 2017;Siregar et al 2019;Yuskianti and Shiraishi 2017). Shabrina et al (2019a) supported this result, which found variances in gene expression in prime sengon plants against sengon plants with gall rust through differential expression gene (DEG) analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Belum terserangnya tiga provenan tersebut terhadap penyakit karat tumor diduga karena lebih tingginya keragaman genetik provenanprovenan tersebut dibandingkan provenan lainya sehingga memiliki tingkat resistensi yang lebih tinggi. Yuskianti & Shiraishi (2017) melaporkan bahwa sengon yang berasal dari Wamena dan Biak (Papua) serta Halmahera (Maluku) mempunyai keragaman genetik yang tinggi dan cluster yang berbeda. Menurut Siregar & Olivia (2012), variasi genetik yang tinggi berpengaruh terhadap kemampuan suatu jenis untuk beradaptasi.…”
Section: B Respon Tanaman Terhadap Serangan Karat Tumorunclassified